Social transformations and knowledge in the context of a water crisis in the province of Córdoba, Argentina - Koberwein, Adrián (2017)
This article analyses the role of knowledge in the production of new social relations and institutional configurations in the context of a water crisis in Sierras Chicas, Córdoba, Argentina. Based on an ethnographic approach; it analyses the way in which factual information of scientific and non-scientific origin, operates as knowledge in two different but complementary ways: on the one hand, it is appropriated and used as the basis of visibility strategies by different groups and non-governmental organizations; on the other hand, it works as the ground for active interventions on the water crisis, generating both cohesive and conflictual relations. The article shows how these relations become embedded in the process of creation of knew institutional arrangements, in which an electoral campaign, the concerns and actions of the inhabitants regarding environmental problems, and the knowledge about «natural processes», among other dynamics, are considered part of a more general process of production of society.